Effect of extrusion processing on the structural, functional, and physicochemical properties of wheat and wheat-based products: A review - Junjie Chen; Qiang Liu; Siqi Zhao; Liping Guo; Xinbo Zhuang; Xuehong Chen; Tingting Tao; Chao Ding (Food Physics)
Wheat is one of the most important cereal crops and a critical ingredient in a wide range of ready-to-eat products, such as bread, noodles, cakes, and snacks, due to its favorable sensory attributes and processing properties. Extrusion, a process commonly used in the food industry, has proven effective in enhancing the nutritional value and functionality of wheat-based products by precisely controlling processing parameters. In this review, we explore the effects that extrusion process parameters have on the structural, functional, and physicochemical properties (e.g., expansion ratio, water absorption index, water solubility index, texture, viscosity, and digestibility) of wheat-based products. We also discuss specific applications of extruded wheat products. The findings of this review highlight how including an extrusion process can improve product quality and advance wheat-based product development in the food industry.